The Green Approach in the Development of Hydrogel for Wound Healing - Perancis, Franceona Fiona; Md Hanif, Muhammad Akmal; Mohammad Fhadlee, Mohammad Fhakrur Radzi; Suradi, Siti Samahani (Multidisciplinary Applied Research and Innovation, 2025)
Hydrogels derived from plant-based mucilage have potential use in biological materials due to their biocompatibility and high water retention capacity. This study aimed to investigate the effect of the modification of hydrogel with the addition of okra mucilage. Two different methods were used: heated (C2) and non-heated (C1) in the extraction of mucilage, and then, subsequently, characterised in terms of measurements of the swelling ratio, Scanning Electron Microscopy (SEM), and antibacterial activity against Staphylococcus aureus (S. aureus). It was found that the morphology of the samples demonstrated the porous microstructure, imparting efficient swelling and solvent penetration. Plus, the addition of the heated-extraction okra mucilage enhances both hydration capacity and antibacterial performance in hydrogels with superior swelling capacity of sample C2 (6797%) compared to C1 (5013%), resulting in stronger antibacterial activity. Therefore, the addition of okra mucilage-based hydrogels has potential as wound-healing biomaterials with superior swelling capacity and mechanical strength.